The Historical Foundation of Religious Moderation in the Qur'an and Its Implications for Contemporary Islamic Education - Mochamad Faidlul Abrori; Muhammad Farih (Tilawah: Journal of Al-Qur'an Studies, 2026)
Religious moderation is a fundamental principle in Islamic teachings that emphasizes justice, balance, and proportionality in understanding and practicing religion. This concept has a strong theological foundation in the Qur’an, particularly through the doctrine of wasathiyyah, which positions Muslims as ummatan wasathan. This article aims to examine the historical foundations of religious moderation in the Qur’an and analyze its implications for contemporary Islamic education. This study employs a qualitative approach using library research, combined with historical analysis and thematic interpretation (tafsīr maudhū‘ī). The data are derived from the Qur’an, classical and contemporary Qur’anic commentaries, Prophetic traditions, and relevant scholarly books and journal articles. The findings reveal that religious moderation in the Qur’an is deeply rooted in the values of justice (‘adl), balance (tawāzun), tolerance (tasāmuh), and humanity (insāniyyah), which were gradually implemented throughout the Makkan and Madinan periods. Furthermore, religious moderation has significant implications for contemporary Islamic education, particularly in strengthening inclusive educational paradigms, integrating moderation values into curricula and learning processes, and enhancing the role of Islamic education in fostering tolerant and inclusive attitudes within plural societies. Therefore, religious moderation serves as a crucial foundation for developing a civilized and contextually relevant Islamic educational system.